THE RELATIONSHIP BETWEEN MORTGAGE FINANCE AND REAL ESTATE DEVELOPMENT IN KENYA (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
Real estate investment plays a crucial role in providing employment opportunities, offering shelter to households, enhancing income distribution and alleviating poverty. One of the most important factors in real estate development, world over, is its financing. Unlike the developed countries that use stocks and bonds, financing of real estate developments in Kenya is predominantly through mortgage financing. This study will seek to find out the relationship between mortgage financing and real estate development in Kenya. This study will adopt an explanatory research design by review of the literature.